2017
DOI: 10.1038/s41598-017-10442-7
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Regulates Txnip and Prevents Intermittent Hypoxia-Induced Vascular Injury

Abstract: Chronic intermittent hypoxia (IH) contributes to obstructive sleep apnea (OSA)-related cardiovascular diseases through increasing oxidative stress. It has been widely recognized that estradiol decreases the risk for cardiovascular disease, but the estrogen replacement therapy is limited for its side effects. Thioredoxin (Trx) and its endogenous inhibitor, thioredoxin-interacting protein (Txnip), are associated with the protective effect of estradiol in some conditions. In this study, we aimed to explore whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…We previously found that E2 suppressed oxidative stress and decreased cell apoptosis in IH-exposed HUVECs 9. In this study, a group of differentially expressed proteins between the IH and IH+E2 group were involved in cellular stress response (such as DNA damage and heat response) based on functional analysis.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…We previously found that E2 suppressed oxidative stress and decreased cell apoptosis in IH-exposed HUVECs 9. In this study, a group of differentially expressed proteins between the IH and IH+E2 group were involved in cellular stress response (such as DNA damage and heat response) based on functional analysis.…”
Section: Resultsmentioning
confidence: 86%
“…CIH induces oxidative stress,9,24 and consequently causes oxidative DNA damage and cytotoxicity, leading to endothelial cell apoptosis. In the study, we exposed HUVECs to 1% O 2 for 5 mins followed by 5 mins at 21% O 2 in the gas phase (equivalent to 6 cycles/hr).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And moreover, MMP13 could increase the secretion of VEGF‐A from endothelial cells, by which it may directly promote angiogenesis and capillary formation and is well correlated with microvascular density. In addition, studies indicated that some mRNAs, such as TXNIP and VCAM‐1 played a pivotal role in glucose toxicity‐induced oxidative effects, microvascular injury, and endothelial dysfunction. Collectively, these gene expression profiles that relating with microvascular endothelial cells function exhibit a substantial changing trend in glucose toxicity exposure, supporting the view that their up‐ and downregulation may be involved in the impairment of IMECs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, estrogen can modulate the immune function of various cell types ( Straub, 2007 ) and possibly interferes with the production of various cytokines, such as interleukin-1β (IL-1β), NF-ÎşB, and tumor necrosis factor-Îą (TNF-Îą) in several systems ( Stein and Yang, 1995 ; Cerillo et al, 1998 ; Evans et al, 2002 ; Sarvari et al, 2011 ). Although estrogen is a critical contributor to gender effects on OSA-associated cardiovascular consequences ( Kapsimalis and Kryger, 2002 ; Lan et al, 2017 ), its role in the development of OSA-related hyperreactive airway diseases in females remains unclear.…”
Section: Introductionmentioning
confidence: 99%